Development of cutting edge geometries for hard milling operations. (January 2015) - Denkena, B.; Köhler, J.; Bergmann, B.
Abstract: Milling of hardened steels is a challenging task for mould and die manufacturing due to the high material strength. One major drawback is the tool wear, which is a result of the high thermo-mechanical stress on the tool. The wear rate can generally be influenced by the tool geometry, coatings and substrates. A further approach is to modify the flank face of the tool, which leads to geometrical limitation of the flank wear. The challenge of this approach is to design flank face modifications, which offer process reliability and increased performance. Against this backdrop a finite element simulation has been constructed to analyze tool stresses. Therefore, different material and friction models were investigated. Based on this simulation a regression model has been developed. Due to the regression model the flank face modifications have been designed and manufactured by laser machining. In cutting tests the potential of the flank face modifications compared to conventional hard milling tools was investigated. The flank face modifications enable the increase of tool life time and the production of workpieces with reduced tensile residual stresses.